2002
DOI: 10.1111/1540-627x.00050
|View full text |Cite
|
Sign up to set email alerts
|

The Successful Product Pioneer: Maintaining Commitment while Adapting to Change

Abstract: Introducing pioneering products is an important entrepreneurial activity and the lifeblood of small businesses, yet previous literature on pioneering and performance in small firms has been inconclusive. Based on data gathered from entrepreneurs in 51 small computer firms, the study found that commitment (entrepreneurial confidence) and adaptability (corporate entrepreneurship and environmental dynamism) were especially beneficial to pioneers. The other three variables (product championing, marketing emphasis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 31 publications
4
59
1
3
Order By: Relevance
“…Also, De Jong and Marsili (2006) have examined innovations in small enterprises with fewer than 100 employees. They argue that process innovation is more widespread in small enterprises than product innovation while Simon et al (2002) found that entrepreneurial condense, adaptability, product championing, market emphasis and technological innovation contributed to performance across all new product introductions in small computer firms. Wolff and Pett (2006), suggest that internationalization and innovator's position have a positive impact on new product improvement in SMEs (Lu and Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, De Jong and Marsili (2006) have examined innovations in small enterprises with fewer than 100 employees. They argue that process innovation is more widespread in small enterprises than product innovation while Simon et al (2002) found that entrepreneurial condense, adaptability, product championing, market emphasis and technological innovation contributed to performance across all new product introductions in small computer firms. Wolff and Pett (2006), suggest that internationalization and innovator's position have a positive impact on new product improvement in SMEs (Lu and Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their flexibility and speed in introducing innovations, small firms would gain advantages from incremental innovations in highly competitive markets . In the case of radical innovations, some authors argue that the financial success of these innovations is larger in large firms than in small ones (Paulson et al, 2007), whereas others argue that they are more easily obtained in small firms because the firm itself could be based on a radical idea (Kanter, 1985;Simon et al, 2002;Stringer, 2000).…”
Section: In Accordance With Henard and Mcfadyen (2005) Different Apprmentioning
confidence: 99%
“…Thus, the concept of PEB contains the ideas of pioneering behaviors (Lumpkin and Dess, 1996;Mueller et al, 2012). Focusing on PEB allow us to capture a broader scope of a firm's strategic posture of positioning itself in anticipation of changes in the market by taking an active role to sharp the future state of its external environment (Kreiser et al, 2013;Lumpkin and Dess, 1996) (Nasution et al, 2011;Rhee et al, 2010;Simon et al, 2002).…”
Section: Direct Effect Of Peb On New Product Development Performancementioning
confidence: 99%